Efektifitas Penegakan Undang-Undang Nomor 16 Tahun 2019 tentang Perubahan Atas Undang-Undang Nomor 1 tahun 1974 Tentang Perkawinan Terhadap Pernikahan Anak di Bawah Umur - Adi Wijaya; Imelda Hasibuan; Rosa Bella (LPPM STIH Awang Long, 2022)
In fact, adolescents under 19 years of age still have to strengthen themselves in terms of education, mental-spiritual, physical endurance to the economy that will support their welfare when they enter the family level. What if the good times as a teenager were taken away because they had to get married at a young age. Underage marriages bring more harm so parents, guardians, who are getting married should stick to the Marriage Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. The author uses the library research method or literature review. This library research research is to conduct research from library books, magazines, journals and articles and sources from the internet that are relevant to the issues discussed.